Bien dans notre peau: Élaboration d’un outil de diagnostic pour informer la conception et l’évaluation de services et partenariats sécuritaires, inclusifs et équitables pour toute personne 2ELGBTQ+ d’expression française au Manitoba - Courcelles, Rémi; Hardy, Stephan; Prada, Kevin (Santé Canada, 2023)

Des nôtres : une analyse des besoins des personnes LGBTQ2S d’expression française du Manitoba - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya (Collectif LGBTQ du Manitoba et Université de Saint-Boniface, 2021)
Cette étude, menée sous l’impulsion du Collectif LGBTQ* du Manitoba, est la première à sonder les besoins de la communauté LGBTQ2S d’expression française au Manitoba (désormais la « Communauté »). L’objectif était de brosser le portrait de la situation actuelle de ses membres de 18 ans et plus quant à 1) leur profil sociodémographique et ethnoculturel; 2) leurs besoins en matière de soutiens sociaux et de soins de santé; 3) leurs perceptions de discrimination ou de stigmatisation, tant par rapport à la langue qu’à l’orientation sexuelle et/ou à l’identité de genre; et 4) leurs priorités pour l’avenir. Par l’entremise d’un sondage en ligne, la Communauté a su nous informer de ses besoins prioritaires, particulièrement en matière de santé mentale et de soutien social.

Mental health status and help-seeking strategies of international students in Canada - de Moissac, Danielle; Graham, Jan Marie; Prada, Kevin; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Canadian Journal of Higher Education, 2020)
International students are at heightened risk of developing psychological distress, yet little research has been conducted on their mental health or support needs. This quantitative study focused on undergraduate students at two mid-sized universities in Manitoba, Canada. Online and paper surveys were completed by 932 participants, of whom 21% identified as international students. This paper, descriptive in nature, outlines the sociodemographic profiles, current mental health status, psychological characteristics, and coping strategies of international students compared to domestic students in each institution. Data show that international students are more likely to report excellent mental health, score higher on the mental health scale, and report higher life satisfaction, higher self-esteem, and more positive body image than domestic respondents. However, they are less likely to talk about their hardships. Providing culturally-adapted supports that take into consideration ethnolinguistic differences, religious practice, and mental health literacy will better meet the needs of international students on campus.

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Living in a liminal space: Experiences of 2SLGBTQ + official language minority Canadians during the COVID-19 pandemic - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Hardy, Stephan; Avanthay-Strus, Jacqueline (Culture, Health & Sexuality, 2023)
The intersecting identities of those identifying with multiple minorities, such as 2SLGBTQ + and ethnolinguistic minorities, bring individuals to have unique experiences, especially concerning health and wellness. This topic is particularly poorly understood among French-speaking official language minority 2SLGBTQ + populations in Canada. Hence, this study was conducted to generate insights into their needs and experiences, through the lens of intersectionality. This quantitative community-based study, a first of its kind in Western Canada, describes the sociodemographic profile, experiences of discrimination and stigmatisation, and needs and challenges pertaining to mental health and social supports of this double minority group. Data were obtained by an online survey conducted in the Canadian province of Manitoba in June 2020. The participant sample was largely homogenous: most were under the age of 55 years, white, educated, and from urban areas. Many reported experiencing dual marginalisation, feeling unaccepted by both of their minority communities (Francophone and 2SLGBTQ+). A sense of isolation, as well as a lack of social connectedness and psychological support, were often reported. Social initiatives and mental health support within environments proactively affirming of the official language of the minority and inclusive of diverse 2SLGBTQ + identities are needed.